2014
DOI: 10.1096/fj.14-263053
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for cannabinoid receptors in the therapeutic action of fenofibrate

Abstract: Cannabinoids are reported to have actions through peroxisome proliferator-activated receptors (PPARs), which led us to investigate PPAR agonists for activity at the cannabinoid receptors. Radio-ligand binding and functional assays were conducted using human recombinant cannabinoid type 1 (CB 1 ) or cannabinoid type 2 (CB 2 ) receptors, as well as the guinea pig isolated ileum, using the full agonist CP55940 as a positive control. The PPAR-a agonist fenofibrate exhibited submicromolar affinity for both receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Recently, Nickolls et al () found that fenofibrate also acts as an agonist of the CB 2 receptor and a partial agonist of the CB 1 receptor. It has been demonstrated that chronic stress leads to widespread reductions in anandamide concentrations throughout the brain, together with decreased CB 1 receptor signal transduction in subcortical structures, such as the hippocampus, while the direct pharmacological activation of the CB 1 receptor produces antidepressant‐like responses in the FST (Hill et al, , , ; Jiang et al, ; Bambico et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nickolls et al () found that fenofibrate also acts as an agonist of the CB 2 receptor and a partial agonist of the CB 1 receptor. It has been demonstrated that chronic stress leads to widespread reductions in anandamide concentrations throughout the brain, together with decreased CB 1 receptor signal transduction in subcortical structures, such as the hippocampus, while the direct pharmacological activation of the CB 1 receptor produces antidepressant‐like responses in the FST (Hill et al, , , ; Jiang et al, ; Bambico et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…8 These include CB1 receptor NAMs such as PSNCBAM-1 ( 2 ) 9 , fenofibrate ( 3 ), 10 and CB1 receptor PAMs ZCZ011 ( 4 ) 11 and GAT211 ( 5 ) 12 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…29 The dopamine transport inhibitor RTI-371 33 and the PPAR-α agonist fenofibrate have also been suggested to act at a CB1R allosteric site. 34 Very recently, we have shown that cannabidiol, the nonpsychoactive constituent of Cannabis sativa , exhibits negative allosteric modulation at CB1R. 35 Additionally, ligands displaying positive allosteric modulation of orthosteric ligand’s binding and function have been reported recently.…”
Section: Introductionmentioning
confidence: 99%